2022
DOI: 10.1002/hpm.3601
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary private health insurance demand by Portuguese seniors before the COVID‐19 pandemic

Abstract: Aims: The Portuguese health system is mainly described as a National Health Service (NHS), but it also has some Bismarckian features. On top of these two layers of health insurance coverage, there is a market for voluntary private health insurance (VPHI). Usually, seniors are not eligible for this type of health insurance and this may serve as a complement or supplement to the NHS. The purpose of this work is to identify the main factors associated with holding a VPHI policy among seniors before the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Demographic and socioeconomic drivers are identical for the two waves of the National Health Survey. As expected, older people are less likely to buy VPHI as found [19,20]. This happens not only as a cream-skimming market strategy by insurance companies but also because primary care contractual goals are favourably biased towards older people [27].…”
Section: Interpretation Of Findingsmentioning
confidence: 59%
See 2 more Smart Citations
“…Demographic and socioeconomic drivers are identical for the two waves of the National Health Survey. As expected, older people are less likely to buy VPHI as found [19,20]. This happens not only as a cream-skimming market strategy by insurance companies but also because primary care contractual goals are favourably biased towards older people [27].…”
Section: Interpretation Of Findingsmentioning
confidence: 59%
“…The oldest study was published in 2003 [17], the author found that some factors associated with buying VPHI such as being older, self-employed, living in urban areas, and receiving high income. Following this study, Tavares [18][19][20] has published some research work on the drivers related to holding VPHI policy in Portugal, focused on the relationship between health insurance demand and lifestyle decisions [18] and on the seniors' segment [19,20]. In this set of empirical work, demographic, socioeconomic, health status, and healthcare utilisation factors were used to explain paying for VPHI.…”
Section: Overview Of the Health Insurance Market And On Vphi In Portugalmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of JKN marked a pivotal moment in Indonesia's healthcare history (Tavares, 2022). The program's overarching goal is to ensure that every Indonesian citizen and eligible resident has access to quality healthcare services without the risk of financial ruin due to medical expenses to achieve universal health coverage ensuring that every Indonesian citizen and eligible resident has access to essential healthcare services regardless of their socioeconomic status or geographic location.…”
Section: Introductionmentioning
confidence: 99%